Terminology and language planning : an alternative framework of practice and discourse - Antia, Bassey Edem (Terminology and lexicography research and practice, 2000)
Changing socio-political landscapes, the dynamics of 'glocalisation', among other factors, are spawning new policy attitudes towards multilingualism, and again putting language planning (LP) on the map - in a manner reminiscent of the 1960s and 1970s. With respect to terminology, this book suggests that to be relevant and sustainable, current LP would have to define its mission as the deregulation of access to specialised knowledge, and correspondingly be founded on substantially different methods and theoretical bases: epistemology and ontology of specialised domains; research on language for.